A note on the occurrence of root lesion nematodes under native sand-prairie plant species in the Regional Municipality of Haldimand-Norfolk, Ontario - McKeown, A.W.; Potter, J.W.; Gartshore, M.E.; Carson, P. (Phytoprotection, 1994)
The root lesion nematode Pratylenchus penetrans, which is the most important plant-parasitic nematode in southern Ontario, has an extremely wide host range. Because of the need to suppress lesion nematodes with cover-crop species which are poor or non-hosts of this parasite, a number of native sand-prairie species were evaluated for susceptibility. Eleven plant species belonging to the families Asclepiadaceae, Asteraceae, Poaceae and Fabaceae were determined to support very low numbers of P. penetrans and consequently to have potential as beneficial cover-crops.